The Bloom syndrome complex senses RPA-coated single-stranded DNA to restart stalled replication forks - Ann-Marie K. Shorrocks (Nature Portfolio, 2021)
The BLM helicase interacts with the topoisomerase TOP3A and RMI1 to form the BTR complex. Here, the authors reveal that this complex contains multiple binding sites for the single-stranded DNA-binding complex RPA, and that RPA-binding stimulates BLM recruitment to stalled replication forks to promote their restart after replication stress.